Cross-domain robustness in visual place recognition: an adversarial-based domain alignment approach - Lin, Yingying (Nanyang Technological University, 2024)
Visual Place Recognition (VPR) serves as an important component in robotic sensing, mainly utilized within navigation systems, such as autonomous vehicles. VPR enables large-scale localization by comparing current query visual cues within a geo-tagged database of previously visited locations. The main approach in VPR is using weak-supervised representation learning to generate compact but discriminative place descriptors, which are then used for image retrieve the closest match location from the database.